Usefulness and misrepresentation of phone surveys on COVID-19 and food security in Africa - Tilman Brück; Mekdim D. Regassa (Food Security, 2022)
We survey efforts that track food security in Africa using phone surveys during the COVID-19 pandemic. Phone surveys are concentrated in a few countries mostly focusing on a narrow theme. Only a few allow heterogeneous analyses across socioeconomic, spatial, and intertemporal dimensions across countries, leaving important issues inadequately enumerated. We recommend that the scientific community focuses on countries (and regions and groups within countries) where the evidence base is thin, and that policymakers in less researched areas attract more research by improving their statistical capacity, openness, and governance.
Keywords: I1; I3; C83; 630; Phone survey; COVID-19; Food security; Africa